Konstrukční návrh osobního výtahu umístěného ve svahu - Látal, Roman (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Bakalářská práce se zabývá konstrukcí výtahu do svahu pod úhlem 25° pro 4 osoby s celkovou nosností 400 kg. Konstrukce je rozdělena do dvou bakalářských prací, přičemţ tato práce je zaměřena na návrh konstrukce kabiny výtahu. Práce obsahuje konstrukční zpracování kabiny a výkresovou dokumentaci.

Bachelor’s thesis is covering a topic of construction of slope elevator with a tilt of 25 degrees for four people with total capacity of 400 kilograms. The construction is divided into two bachelor´s theses and this thesis is focused to the design of cabin construction. This thesis contains constructional design of the cabin and its technical drawings.
Design of hillside elevator
Keywords: Šikmý výtah; kabina; svahový výtah; Elevator with tilt; cabin; slope elevator